2013
DOI: 10.1002/jctb.4251
|View full text |Cite
|
Sign up to set email alerts
|

Salt‐free production of γ‐aminobutyric acid from glutamate using glutamate decarboxylase separated from Escherichia coli

Abstract: BACKGROUND: Gamma(γ )-aminobutyric acid (GABA) has been used extensively in pharmaceuticals and functional foods and is also a building block for bioplastics. GABA is produced from glutamate through decarboxylation catalyzed by glutamate decarboxylase (GAD). The reaction medium should be kept acidic because a pH rise resulting from the reaction inactivates the enzyme catalyst, which is active only at acidic pH. The use of conventional buffers and acids inevitably accompanies salts, which cause serious problems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Purified GAD and natural and recombinant microorganisms expressing GAD have been employed for the conversion of glutamate monosodium salt (MSG) or glutamic acid to GABA. Recent studies have suggested that GABA can be efficiently produced from L-glutamate by some lactic acid bacteria (LAB) [ 7 , 8 ] and recombinant Escherichia coli [ 5 , 9 , 10 ]. Basically, it is needed to develop additional enzymatic and whole cell mediated conversion of MSG into GABA when fermentation-derived MSG is used for the production of GABA.…”
Section: Introductionmentioning
confidence: 99%
“…Purified GAD and natural and recombinant microorganisms expressing GAD have been employed for the conversion of glutamate monosodium salt (MSG) or glutamic acid to GABA. Recent studies have suggested that GABA can be efficiently produced from L-glutamate by some lactic acid bacteria (LAB) [ 7 , 8 ] and recombinant Escherichia coli [ 5 , 9 , 10 ]. Basically, it is needed to develop additional enzymatic and whole cell mediated conversion of MSG into GABA when fermentation-derived MSG is used for the production of GABA.…”
Section: Introductionmentioning
confidence: 99%
“…Since the crystal structures of E. coli GADs revealed the structural basis for its optimal activity at acidic pH, several mutants with high activity toward more alkaline pH values have been constructed to improve GABA production (Choi et al 2015 ; Shi et al 2014 ; Thu Ho et al 2013 ). On the other hand, hydrochloric acid, sodium acetate buffer and acidic cation-exchange resins were used to maintain the acidic condition during reaction from MSG into GABA, and the conversion efficiency were remarkably improved (Dinh et al 2014 ; Park et al 2013 ; Plokhov et al 2000 ). However, these methods were also unsatisfactory for the following separation and purification of GABA due to the introduction of the high amount of salts or resins.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of LlGAD with other GAD proteins showed LlGAD contained a highly conserved motif (HVDAAFGG) that belongs to the PLP-dependent decarboxylase superfamily [15]. The domain includes a conserved lysine residue essential for PLP binding discovered in LlGAD (K 277 ), and this lysine residue was located with the adjacent histidine residue [16]. In addition, the active site residues involved in promoting decarboxylation were also present in LlGAD (T 213 and D 244 ) [15] (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The optimum induction conditions for the expression of GAD in E. coli were investigated by single-factor experimental design, i.e. the recombinant cells induced by different concentrations of IPTG (0.4, 0.7, 1.0, 1.3 and 1.6 mmol L ¡1 ) added to the exponentially growing cells, different induction times (10,12,16, 18 and 20 h) and different induction temperatures (26,28,30, 32 and 34 C). The single-factor experiments were conducted in triplicate for each group and mean values with standard deviations ( §SD) were calculated for GABA production and cell density.…”
Section: Optimization Of Induction Conditionsmentioning
confidence: 99%
See 1 more Smart Citation